Bedtime Window: A Field Study Connecting Bedrooms of Long-Distance Couples Using a Slow Photo-Stream and Shared Real-Time Inking - Kučera, Jan; Scott, James; Lindley, Siân; Olivier, Patrick (CHI, 2021)
We present a system for connecting partners in long-distance relationships in bedrooms and at bedtime, a space and time that most couples share. Unlike communications explicitly initiated by users, our system is always-on, staying in the background and enabling remote presence without constant use. We present findings from a field study in which the system was deployed into participants’ bedrooms. The system includes an automated photo-stream (rather than video), which was found to provide a balance between the feeling of presence and privacy, and to remove the pressure to communicate. The system also includes a real-time shared inking canvas with disappearing ink, which was found to provide a rich versatile medium allowing for new patterns of communication, live interventions, and collaborative drawing. Learnings from how our system balances privacy and remote connectedness may also have relevance for other domains such as remote healthcare and education.